PENGARUH PERSEPSI TAX AMNESTY, PERTUMBUHAN EKONOMI DAN TRANSFORMASI KELEMBAGAAN DIREKTORAT JENDERAL PAJAK PADA PENERIMAAN PAJAK - Gunawan, Andri; Sukartha, I Made (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
This study aims to determine the factors that affect tax revenues in 2015 in the North Badung Small Tax Office, allegedly influenced by tax amnesty, economic growth and institutional transformation of the Directorate General of Taxation. This research was conducted in the North Badung Small Tax Office. The samples studied were 98 taxpayers. The sampling method used slovin with accidental sampling technique sampling. Data collected through questionnaires. The analysis technique used is multiple linear regression analysis. Based on the analysis concluded that the tax amnesty, economic growth and institutional transformation of the Directorate General of Taxation positive effect on tax revenue in 2015.
Keywords: Tax Amnesty, Economic Growth, Institutional Transformation Directorate General of Tax, Tax Revenue